2011
DOI: 10.1186/1471-2148-11-333
|View full text |Cite
|
Sign up to set email alerts
|

Demographic history, genetic structure and gene flow in a steppe-associated raptor species

Abstract: BackgroundEnvironmental preferences and past climatic changes may determine the length of time during which a species range has contracted or expanded from refugia, thereby influencing levels of genetic diversification. Connectivity among populations of steppe-associated taxa might have been maximal during the long glacial periods, and interrupted only during the shorter interglacial phases, potentially resulting in low levels of genetic differentiation among populations. We investigated this hypothesis by exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 67 publications
(85 reference statements)
3
27
0
Order By: Relevance
“…C. hudsonius) and 'young' species (C. aeruginosus), is likely not due to the age of origin or a selective sweep. Thus, taking the results from this study and previous harrier molecular studies into account (Garcia et al, 2011;Fuchs et al, 2014), continuous fluctuations in prey availability leading to recurrent variations in harrier population sizes may be the driver behind low genetic diversity observed within Circus species.…”
Section: Biogeographic Inferencesmentioning
confidence: 84%
See 1 more Smart Citation
“…C. hudsonius) and 'young' species (C. aeruginosus), is likely not due to the age of origin or a selective sweep. Thus, taking the results from this study and previous harrier molecular studies into account (Garcia et al, 2011;Fuchs et al, 2014), continuous fluctuations in prey availability leading to recurrent variations in harrier population sizes may be the driver behind low genetic diversity observed within Circus species.…”
Section: Biogeographic Inferencesmentioning
confidence: 84%
“…Previous phylogeographic studies on the Black Harrier (Fuchs et al, 2014) and the Montagu's Harrier (Garcia et al, 2011) have shown low (Garcia et al, 2011) to no (Fuchs et al, 2014) genetic variation among populations of both these species and very little to no geographic structure. Here, two harrier taxa were sampled from widespread localities of their 20 breeding distribution and they show similar trends.…”
Section: Biogeographic Inferencesmentioning
confidence: 97%
“…Hence, this result also suggests a high capacity for genetic exchange between populations, which would lead to relatively low genetic differentiation between populations of Western Europe. Such low degree of population genetic structuring has been recently described in this species (García et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Dispersal is a major biological process influencing large‐scale population dynamics and evolutionary processes (Garant et al , Clobert et al , Garcia et al ). Theoretically, the evolution of dispersal is associated with a tradeoff between fitness‐related costs and benefits (Bowler and Benton , Clobert et al ).…”
mentioning
confidence: 99%